Incorporating Sustainable Education in the Undergraduate Curriculum: The Experience of a Young University in Singapore - Mokhtar, Intan Azura; Chong, Ethan Yih Tng; Jusuf, Steve Kardinal (European Journal of Sustainable Development, 2023)
In recent years, learning about sustainable development and sustainability has become an increasingly significant component in universities’ degree programs and curricula. As the world races to achieve the 17 United Nations’ sustainable development goals (SDGs) by the year 2030 and abide by the framework proposed by the Paris Agreement ratified in 2015, our educational landscapes have simultaneously evolved. In universities, lessons in and opportunities for sustainable development and sustainability have redefined the university curricula and set the trajectory for our young people to take the lead in co-creating solutions for a better world. In this paper, background information of Singapore, a small city-state in Southeast Asia, is first presented, against the backdrop of how the nation’s national constraints that are aligned to the UN SDGs have shaped its national agenda and national education, including its higher education landscape. This is followed by a brief discourse of curriculum initiatives that revolved around themes of sustainable development and sustainability in a young university in Singapore. These initiatives and projects were driven by the desire to provide a university education that is relevant and able to address current local, regional, and global demands, and carried out with interdisciplinarity and sustainability as beacons. Keywords: higher education; Singapore; sustainable development; sustainability; undergraduate education.